Toll-like receptors as a therapeutic target in cancer, infections and inflammatory diseases (2020)
Toll-like receptors (TLRs) are widely expressed pattern recognition receptors that bind to conserved molecular patterns expressed by pathogens and damaged cells. After recognition, activated TLRs induce the expression of various proinflammatory and antiviral molecules. Thus, TLRs are potential targets for treatment strategies aimed at boosting the adaptive immune response to vaccines, controlling infections, enhancing immune responses during tumor treatment and attenuating immune responses in inflammatory disorders. This Special Report examines the potential of TLRs as targets for the treatment of cancer, infections and inflammatory diseases. Here, we make a particular emphasis on molecules capable of modulating TLRs and their therapeutic applications.